Introduction to NJWLS 2021-3 - Buch, Anders (Nordic Journal of Working Life Studies, 2021)
This issue of Nordic Journal of Working Life Studies presents six new research articles from the Nordic countries. The first article of the issue is Working Environment Activities in Hospitals: Expansion of Scope and Decentralization of Responsibility by Per-Christian Borgen and Bente Vibecke Lunde. Borgen and Lunde’s study explores how legislative working environment regulations are understood and handled by actors responsible for the working environment in three hospitals in Norway (...)